Implementation of Financial Report Preparation in Small and Medium Enterprises (SMEs) Fostered by DEKRANASDA West Java - Hernawati, Nopi; Nurhayati, Nurhayati; Maemunah, Mey (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2026)
This study aims to 1) Identify the form of accounting implementation based on the EMKM Financial Accounting Standards (SAK EMKM) in Small and Medium Enterprises (SMEs) fostered by DEKRANASDA West Java, and 2) Determine whether the accounting implementation in these SMEs has been in accordance with SAK EMKM. The type of data used is qualitative data, in the form of a questionnaire or statements provided to SME entrepreneurs fostered by DEKRANASDA West Java regarding the implementation of accounting based on the Financial Accounting Standards (SAK). The data analysis uses a descriptive method. The results of the study show that the form of accounting implementation in SMEs fostered by DEKRANASDA West Java in Bandung City and Bandung Regency is still very simple, and on average, it does not comply with the Financial Accounting Standards, as many have not met the stages of the accounting cycle. The challenges faced in preparing financial reports include insufficient technical knowledge in preparing such reports, especially based on SAK, as well as the lack of awareness and discipline among SMEs regarding the importance of complete and standard-compliant financial reports. These reports are essential tools for evaluating the operational results of their businesses. The understanding of SME entrepreneurs fostered by DEKRANASDA West Java regarding the Financial Accounting Standards is still lacking. Overall, the financial report presentation among SME entrepreneurs is approximately 50.72%, which meets the compliance standards based on the Financial Accounting Standards (SAK).